Upaya Guru Dalam Meningkatkan Prestasi Belajar Peserta Didik melalui Metode Pembelajaran Problem Based Learning - Nursabaha, Sarifa (Institut Agama Islam Negeri (IAIN) Bone, 2018)
This article discusses the efforts of Teachers in improving the learning achievements of Students Learning through Problem Based Learning. Problem Based Learning (PBL) is a method of learning that is beriorentasi to solve the problem. Problem Based Learning (PBL) as a model of learning is trying present problematic situations share of authentic and meaningful to learners, which can be enabled in the conduct of the investigation. The problem is contained in the Problem Based Learning (PBL) is a real problem faced in everyday life. The problem is taken from the environment where learning was held. Application of PBL Method can improve learning achievement. This occurs due to the efforts of the Teachers are earnest efforts increased the learning achievements of Students through pembelajarn LBC. Problem Based Learning (PBL) applied to teachers in the process of teaching and learning by utilizing the concept of communication much direction to create an atmosphere of education in creative, dynamic, and so created the learning achievements dialogis satisfactory. In the process of teaching and learning, the teacher has a duty to encourage, guide, and provide learning facilities for learners to achieve objectives (achievers). Teachers have a responsibility to see everything that happens in the classroom to help the process of the development of the learners.